CTNI-09. A PHASE I HEALTHY VOLUNTEER STUDY ON THE RELATIVE BIOAVAILABILITY AND FOOD EFFECT OF CAPSULE AND GRANULE FORMULATIONS OF SELUMETINIB. (9th November 2020) - Cohen-Rabbie, Sarit; Mattinson, Alexandra; So, Karen; Wang, Nan; McBride, Eileen; Vishwanathan, Karthick; Goldwater, Ronald
Abstract: Selumetinib (AZD6244, ARRY-142886) is an oral, potent and highly selective allosteric MEK 1/2 inhibitor approved by the FDA as a capsule formulation for treatment of pediatric patients ≥ 2 years old with neurofibromatosis type 1 and symptomatic, inoperable plexiform neurofibromas. A new granule formulation is being developed to support dose flexibility and for patients unable to swallow capsules. This Phase I, open-label, single-center, randomized crossover pharmacokinetics study (NCT03649165) investigated the new granule versus capsule formulation in both fasted and fed (low-fat) states. Twenty-four healthy adult male volunteers were randomized to receive single-dose selumetinib in one of four treatment sequences: 25 mg granule (fasted); 50 mg capsule (fasted); 25 mg granule (fed); and 50 mg capsule (fed). Primary endpoint: to compare pharmacokinetics of the formulations in fasted state. Secondary endpoints: pharmacokinetics of the formulations in fasted versus fed states, granule palatability, safety and tolerability. In fasted state, a slight delay in absorption of selumetinib by ~0.60 h, with geometric mean ratios (90% CI) of 0.65 (0.58, 0.74) for Cmax/dose and 0.87 (0.81, 0.92) for AUC/dose, was detected when administered as granule versus capsule. For granule in fed versus fasted states, geometric mean Cmax and AUC ratios (90% CI) were 0.61 (0.51, 0.72) and 0.97 (0.91, 1.02). For capsule in fed versus fasted states, geometric mean Cmax and AUC ratios (90% CI) were 0.40 (0.33, 0.48) and 0.62 (0.55, 0.70). Granule palatability was acceptable; volunteers indicated they would take it again. Selumetinib was well-tolerated; for both formulations, few adverse events of mild intensity were reported; dry eyes (fasted) versus dry eyes and rhinorrhea (fed) were most frequent. This was the first study to test the granule formulation in humans; results indicate the granule formulation has similar AUC to the capsule formulation and minimal food effect, supporting planned clinical trials in pediatric patients.